From Sequence to Stability: Rational Insulin Design via Genetic Algorithms and Deep Learning Models in Structural Bioinformatics - Gomes, Mateus R.; Fruet, Gabriel Vasconcelos; Medeiros, Ingryd; da Costa, Roner F.; Bezerra, Eveline M.; G. Gomes, Danielo (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
Insulin’s therapeutic efficacy is hindered by its thermal instability, a major limitation in global diabetes treatment, especially in regions lacking reliable refrigeration. Here we present an in silico protein design pipeline that integrates a multi-objective genetic algorithm with deep learning models to engineer insulin variants with enhanced thermostability and reduced aggregation propensity. The algorithm evolves populations of mutated insulin sequences, evaluated by TemBERTure for thermostability and Aggrescan3D for solubility, incorporating ESMFold for 3D structure prediction. A microservices architecture using Docker ensures scalable and efficient execution. Our results identify candidate variants that maintain high sequence identity and preserve key functional motifs while showing superior biophysical properties. These findings illustrate how the combination of evolutionary algorithms and protein language models can support rational, data-driven strategies in protein engineering. The source code and reproducible experiments are publicly available at https://github.com/gabrielfruet/protein-aggregation .